Fintech’s Help to Rural Revitalization of commercial Banks-a Aase Study of Agricultural Bank of China - Huang Xin (SHS Web of Conferences)
The rapid development of global fintech has changed the traditional financial mode and accelerated the change of the traditional credit intermediary function of commercial banks. Fintech not only brings challenges to commercial banks but also provides new opportunities for commercial banks to develop new business models and innovative businesses and products. With the execution of the national rural revitalization strategy, all rural areas are leveraging their local natural resources to cultivate new industries; consequently, rural sectors continue to innovate and exhibit diversified development. Rural industries play a pivotal role in driving rural revitalization while simultaneously expanding financial demands within these communities. Finance is crucial for promoting regional economic development. At this critical juncture in advancing the “three rural issues,” commercial banks in China should assume their responsibilities by fully utilizing their advantages and increasing support for these areas. The research focuses on analyzing the Agricultural Bank of China as a case study to explore its application of financial technology and its impact on supporting rural revitalization efforts. It summarizes both the strengths and weaknesses of commercial banks in facilitating this process while offering optimization suggestions that can serve as reference points for other banks assisting farmers.